The influence of the type of graphite on the size of reduced graphene oxide - Drewniak, Sabina Elżbieta; Drewniak, Łukasz (Photonics Letters of Poland, 2022)
Reduced graphene oxide is a very attractive material for sensor applications. It exhibits high conductivity at room temperature and high specific surface area. Since it can be produced in many ways, its properties can be influenced by the fabrication method. In this paper, we investigated the influence of graphite precursors (flake, scalar and synthetic) on the size of reduced graphene oxide. We have shown that the size of the precursor determines the size of the obtained rGO. We have noted that the larger graphite size, the larger rGO size. Full Text: PDF References R. Peng, Y. Li, T. Liu et al., "Reduced graphene oxide/SnO2@Au heterostructure for enhanced ammonia gas sensing", Chem. Phys. Lett., 737, 136829 (2019). CrossRef S. Pei and H. M. Cheng, "The reduction of graphene oxide", Carbon N. Y., 50, 9 (2012). CrossRef N. Sharma, V. Sharma, R. Vyas et al., "A new sustainable green protocol for production of reduced graphene oxide and its gas sensing properties", J. Sci. Adv. Mater. Devices, 4, 3 (2019) CrossRef R. Tarcan, O. Todor-Boer, I. Petrovai, C. Leordean, S. Astilean, I. Botiz, "Reduced graphene oxide today", J. Mater. Chem. C, 8, 4 (2020). CrossRef X. Jiao, Y. Qiu, L. Zhang, and X. Zhang, "Comparison of the characteristic properties of reduced graphene oxides synthesized from natural graphites with different graphitization degrees", RSC Adv., 7, 82 (2017). CrossRef J.A. Quezada-Renteria, C.O. Ania, L.F. Chazaro-Ruiz, J.R. Rangel-Mendez, "Influence of protons on reduction degree and defect formation in electrochemically reduced graphene oxide", Carbon N. Y., 149 (2019). CrossRef H. Gao, Y. Ma, P. Song, J. Leng, Q. Wang, "Characterization and cytocompatibility of 3D porous biomimetic scaffold derived from rabbit nucleus pulposus tissue in vitro", J. Mater. Sci. Mater. Electron., 32, 8 (2021). CrossRef A.T. Lawal, "Graphene-based nano composites and their applications. A review", Biosens. Bioelectron., 141, 111384, (2019). CrossRef E. Aliyev, V. Filiz, M.M. Khan, Y.J. Lee, C. Abetz, V. Abetz, "Structural Characterization of Graphene Oxide: Surface Functional Groups and Fractionated Oxidative Debris", Nanomaterials, 9, 8 (2019). CrossRef S. Sali, H.R. Mackey, A.A. Abdala, "Effect of Graphene Oxide Synthesis Method on Properties and Performance of Polysulfone-Graphene Oxide Mixed Matrix Membranes", Nanomaterials, 9, 5 (2019). CrossRef G. Lu, L.E. Ocola, J. Chen, "Reduced graphene oxide for room-temperature gas sensors", Nanotechnology, 20, 44 (2009). CrossRef C. Botas, P. Alvarez, C. Blanco et al., "Critical temperatures in the synthesis of graphene-like materials by thermal exfoliation–reduction of graphite oxide", Carbon N. Y., 52, 2013. CrossRef